2020
DOI: 10.34172/npj.2021.03
|View full text |Cite
|
Sign up to set email alerts
|

Herbal antioxidants and renal ischemic-reperfusion injury; an updated review

Abstract: Renal ischemia-reperfusion (RIR) is a pathological condition due to transient restriction of blood flow to the kidneys, which is followed by the subsequent recovery of perfusion and re-oxygenation. RIR injury contributes to the progression of renal dysfunction including acute kidney injury (AKI) in native and renal allograft transplant. The generation of reactive oxygen species (ROS) during oxidative stress contributes to the occurrence of RIR. Hence, the use of antioxidant compounds can improve oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 89 publications
1
11
0
Order By: Relevance
“…I/R injury also shows infl ammatory changes (27). This alteration worsens the conditions due to the accumulation of immune cells, and infl ammatory intermediaries to the tissues injured by ischemia/ reperfusion (28,29). Similar results were observed in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…I/R injury also shows infl ammatory changes (27). This alteration worsens the conditions due to the accumulation of immune cells, and infl ammatory intermediaries to the tissues injured by ischemia/ reperfusion (28,29). Similar results were observed in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Findings of a study have revealed that antioxidant plant-derived compounds could diminish complications due to oxidative stress and apoptosis and could enhance antioxidant enzymes activity (19). It has also been affirmed that treatment by flavone (20) and flavonoid (21) mitigates the renal dysfunction, oxidative stress, and fibrosis in diabetic rats, and inhibits inflammation and apoptosis in the kidney tissue.…”
mentioning
confidence: 99%
“…It has also been explored that P. harmala leaf extracts benefit from antioxidant (25), antibacterial (26,27), and cytotoxic (28) activities due to polyphenol compositions. Considering the effective role of alkaloids and flavonoids in the inhibition of apoptosis (19)(20)(21)(22)(23) and very scant investigations of the anti-apoptotic properties of P. harmala, the current research was undertaken to evaluate the anti-apoptotic effect of the leaf extract of P. harmala, based on its alkaloids and flavonoids, in type 2 diabetic model rats.…”
mentioning
confidence: 99%
“…AGEs formation inhibition was also indicated in vitro by unprocessed and processed magnolia bark extract containing magnolol [57]. The beneficial effects of magnolol on the kidneys were mentioned likewise in other, non-diabetic research models that analyzed other markers of kidney damage related to apoptosis and oxidative stress [58,59]. Antidiabetic activity and the effect of Magnolia extracts on the basic parameters of oxidative stress in in vitro model lines can be found in Table 3a and antidiabetic activity and the effect of Magnolia extracts on the basic parameters of oxidative stress and lipids in in vivo animal models can be found in Table 3b.…”
Section: Magnolol and Diabetic Nephropathymentioning
confidence: 99%